Signatures of mesospheric particles in ionospheric data - Friedrich, M.; Torkar, K.M.; Singer, W.; Strelnikova, I.; Rapp, M.; Robertson, S. (München : European Geopyhsical Union, 2009)
The state of the ionosphere during the 2007 ECOMA/MASS campaign is described by in-situ observations by three sounding rockets launched from the Andøya Rocket Range and by ground based observations. The ground based measurements included the incoherent scatter radar EISCAT near Tromsø (both on UHF and VHF), as well as an MF radar, a meteor radar and an imaging riometer all located in the close vicinity of the rocket range. The pronounced electron density bite-outs seen by two of the rockets could not be detected from the ground, but the associated PMSE (Polar Mesospheric Summer Echoes) provide indirect evidence of pronounced perturbations of mesospheric electron densities. publishedVersion